86.3k views
3 votes
Square root of 2 divided by the cube root of 2

User Filsa
by
5.8k points

2 Answers

3 votes

ANSWER


\frac{ √(2) }{ \sqrt[3]{2} } = \sqrt[6]{2}

EXPLANATION

We want to simplify


\frac{ √(2) }{ \sqrt[3]{2} }

We rewrite in exponential form to get:


\frac{ √(2) }{ \sqrt[3]{2} } = \frac{ {2}^{ (1)/(2) } }{{2}^{ (1)/(3) } }

Recall the quotient rule of exponents:


\frac{ {a}^(m) }{ {a}^(n) } = {a}^(m - n)

We apply this rule to get:


\frac{ √(2) }{ \sqrt[3]{2} } = {2}^{ (1)/(2) - (1)/(3) }

Simplify:


\frac{ √(2) }{ \sqrt[3]{2} } = {2}^{ (3 - 2)/(6) }


\frac{ √(2) }{ \sqrt[3]{2} } = {2}^{ (1)/(6) }


\frac{ √(2) }{ \sqrt[3]{2} } = \sqrt[6]{2}

User Taemyr
by
5.8k points
3 votes

Answer:
\sqrt[6]{2}

Explanation:

You know that the expression is
\frac{√(2)}{\sqrt[3]{2}}

By definition we know that:


\sqrt[n]{a}=a^{(1)/(n)

You also need to remember the Quotient of powers property:


(a^n)/(a^m)=a^((n-m))

Therefore, you can rewrite the expression:


=\frac{2^{(1)/(2)}}{2^{(1)/(3)}}

Finally, you have to simplify the expression. Therefore, you get:


=2^{((1)/(2)-(1)/(3))}\\=2^{(1)/(6)}\\=\sqrt[6]{2}

User Aman Adhikari
by
6.2k points